2007
DOI: 10.4049/jimmunol.179.11.7800
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Functions as an Adhesion Molecule to Support Eosinophil Rolling and Adhesion under Conditions of Flow

Abstract: Allergic inflammation involves the mobilization and trafficking of eosinophils to sites of inflammation. Galectin-3 (Gal-3) has been shown to play a critical role in eosinophil recruitment and airway allergic inflammation in vivo. The role played by Gal-3 in human eosinophil trafficking was investigated. Eosinophils from allergic donors expressed elevated levels of Gal-3 and demonstrated significantly increased rolling and firm adhesion on immobilized VCAM-1 and, more surprisingly, on Gal-3 under conditions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 51 publications
4
104
1
1
Order By: Relevance
“…Previous in vitro studies have demonstrated that galectin-3 mediates the adhesion of neutrophils to the endothelium by directly cross-linking them (29,47), raising the possibility that galectin-3, in agreement with our present data, initiates neutrophil adhesion to the endothelium during streptococcal pneumonia. Indeed, such a function for galectin-3 as an adhesion molecule has been recently suggested for eosinophils and breast carcinoma cells (70,71). Furthermore, the group of Hughes has demonstrated that galectin-3 enhances the migration of breast carcinoma cells through a three-dimensional matrix (72).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous in vitro studies have demonstrated that galectin-3 mediates the adhesion of neutrophils to the endothelium by directly cross-linking them (29,47), raising the possibility that galectin-3, in agreement with our present data, initiates neutrophil adhesion to the endothelium during streptococcal pneumonia. Indeed, such a function for galectin-3 as an adhesion molecule has been recently suggested for eosinophils and breast carcinoma cells (70,71). Furthermore, the group of Hughes has demonstrated that galectin-3 enhances the migration of breast carcinoma cells through a three-dimensional matrix (72).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the group of Hughes has demonstrated that galectin-3 enhances the migration of breast carcinoma cells through a three-dimensional matrix (72). Notably, Rao et al recently demonstrated that galectin-3 is presented on the surface of IL-1␣-stimulated endothelial cells (71). In addition, our previous microscope observations suggest that the occurrence of extracellular galectin-3 oligomerization appears to be concentrated at the interface of endothelium and adherent neutrophils, especially those localized at tricellular corners, where the borders of three endothelial cells intersect (47).…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 (Gal-3) has a crucial role in eosinophil recruitment and airway allergic inflammation of mice [21]. In humans, eosinophils from allergic donors express elevated levels of Gal-3, which co-localizes with α integrin and increase the rolling and firm adhesion of eosinophils on the VCAM-1 of endothelial cells [22].…”
Section: Eosinophil Migration and Infiltration To Tissuesmentioning
confidence: 99%
“…Galectin-3 mediated angiogenesis depends on the growth factors VEGF and bFGF (Markowska et al, 2010). Another interesting function of galectin-3 is the chemotattraction of monocytes via a G-protein coupled receptor pathway and the role in eosinophil rolling to sites of inflammation (Rao et al, 2007;Sano et al, 2000). Most of those functions can only be performed by full length galectin-3 showing the importance of glycan binding and oligomerisation of the protein (Markowska et al, 2010;Sano et al, 2000).…”
Section: Selected Examples Of Cell Adhesion and Motility Regulated Bymentioning
confidence: 99%